PENGARUH GAYA MENGAJAR TERHADAP DAYA TAHAN KARDIOVASKULER SEBAGAI HASIL BELAJAR EKSTRAKURIKULER PENCAK SILAT - Ni Luh Putu Spyanawati (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2013)
Pencak Silat subject that was taught by coach at SMP Negeri I Susut wasn’t effective. Bbecause the coach had a lessattention to the ability of the students. This research aimed to compare between two learning styles of Pencak Silatsubject through the test results of jurus tunggal. This research used 2 x 2 factorial. Two way anova used to analyzethe data. The results showed that the normality test and homogenity was normal and homogenous distribution. Thetwo way anova showed a significant differences between four groups then followed by LSD test. LSD test showedthat: (1) learning outcomes of the students that used mastery learning styles have the best result between others(2) learning outcomes of the students who was taught by mastery learning style was similar to the students that wastaught by inclusion style with low cardiovascular endurance, (3) learning outcomes of the students who had highcardiovascular endurance, was higher than students who had low cardiovascular endurance that was taught bymastery learning styles, (4) learning outcomes of the students who had a high cardiovascular endurance, similar tothe learning outcomes of students who had low cardiovascular endurance on inclusion style, and (5) there was aninteraction between learning styles and cardiovascular endurance on pencak silat learning outcomes.Keywords: Learning Outcomes, Jurus Tunggal Pencak Silat, Mastery Learning, Inclusion, Cardiovascular.